2003
DOI: 10.1254/jphs.93.204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zaleplon, a Non-benzodiazepine Hypnotic, on Melatonin Secretion in Rabbits

Abstract: Abstract. Melatonin, a major hormone secreted by the pineal gland, is known to play an important role in regulation of the circadian rhythm. (N-[3-(3-cyanopyrazolo[1,5-a]pyrimidin-7-yl)phenyl]-N-ethylacetamide (zaleplon) is a non-benzodiazepine hypnotic that acts via the benzodiazepine site of the GABA A receptor. In the present study, we investigated the effect of zaleplon on melatonin secretion in rabbits using RIA and compared the effect to triazolam and zopiclone. Zaleplon increased a dose-dependent concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
1
6
0
Order By: Relevance
“…The physiological concentrations of melatonin in plasma of rabbits were previously estimated by radioimmunoassay (RIA) as 22.7 pg/ml [ 54 ], that is approximately equivalent to 10 −10 M. In our previous work [ 41 ], we used a concentration of melatonin close to physiological levels (10 −9 M) and higher concentrations (10 −6 M and 10 −3 M) to study its effect on development of rabbit embryos recovered at different stages. It is concluded from this study that a 10 −3 M concentration of melatonin for morulae embryos recovered from rabbit does at 72 hr post-insemination is optimal.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological concentrations of melatonin in plasma of rabbits were previously estimated by radioimmunoassay (RIA) as 22.7 pg/ml [ 54 ], that is approximately equivalent to 10 −10 M. In our previous work [ 41 ], we used a concentration of melatonin close to physiological levels (10 −9 M) and higher concentrations (10 −6 M and 10 −3 M) to study its effect on development of rabbit embryos recovered at different stages. It is concluded from this study that a 10 −3 M concentration of melatonin for morulae embryos recovered from rabbit does at 72 hr post-insemination is optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we have also reported that zaleplon is characterized by a reduced amnesic liability, which may be due to its low affinity for the benzodiazepine site of the GABA A receptor in the hippocampus (7). Additionally, it would seem that zaleplon may promote melatonin secretion, suggesting an influence of zaleplon on chronobiology (8).…”
Section: Introductionmentioning
confidence: 96%
“…One study investigated the effect of zopiclone on circadian rhythms. In this study, which compared the effect of zaleplon to triazolam and zopiclone on melatonin secretion in rabbits, zopiclone did not affect plasma melatonin levels (Noguchi et al, 2003). Zaleplon increased a dose-dependent concentration of melatonin in rabbit plasma collected at 30 min after intravenous administration at doses of 1 and 2 mg/kg.…”
Section: Effect On Sleep Pattern and Sleep Regulationmentioning
confidence: 68%